Evaluasi Pengobatan pada Pasien Geriatrik Rawat Inap dengan Stroke di RS Elizabeth Situbondo Periode November 2022‒Agustus 2023 - Norcahyanti, Ika; Firandi, Adelia; Mauladi, Zainol Ihsan; Machlaurin, Afifah (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2025)
Potentially Inappropriate Medicines (PIMs) cause a significant issue, particularly when dealing with elderly patients. Aging in the elderly results in a decline in physiological body functions, impacting the response to medications. Furthermore, aging leads to decreased elasticity of blood vessels, increasing the risk of cardiovascular diseases such as stroke. The management of stroke requires special attention to minimize the risk of complications and enhance recovery opportunities. This study aims to analyze patient profiles, treatment profiles, and evaluate the treatment based on the Beers Criteria 2019. It is a retrospective descriptive study using a cross-sectional research design and purposive sampling technique for sample selection. The study sample includes elderly patients diagnosed with stroke who were hospitalized at RS Elizabeth Situbondo. Patient medical record data was collected through a specifically designed Data Collection Sheet (DCS) to evaluate drug utilization in these patients. The research findings indicate that the patients are predominantly male (53.2%), aged 60-69 (62.3%), and have a Length of Stay of 1-6 days (84.4%). All patients have payment status through BPJS. The treatment profile involves the administration of medications for stroke management, with ticagrelor as the primary drug (66.2%) and citicoline as the most commonly prescribed supplementary drug (97.4%). Treatment evaluation identified 193 events of drug use that potentially met the 2019 Beers Criteria. The highest category was potentially inappropriate drugs (134 events), with pantoprazole being the most commonly used drug (71 events).